Analisis Pengembangan dan Implementasi System E-learning Untuk Meningkatkan pengetahuan Agent Menggunakan Metode ADDIE Model (Study Kasus: PT.Global Infotech Solution) - Nansy Stephanie Mongi; Hendry Hendry (Universitas Budi Darma, 2021)
The development of e-learning system ini companies is very important in the learning process and training of employees or agents to achieve company goals. Like at PT. Global Infotech solution where the learning process still uses manuals so that it hinders learning because to hold training is quite large ini incurring costs for agents who are outside the region. Therefore companies need an e-learning system to help the employee agent learning process to be more affective. E-learning system have been developed and implemented using the moodle platform, which is one of the learning management system. The development method used is the ADDIE (Analysis, Design, Implementation, Evaluation) model so that it is faster ini developing an e-learning system platform according to user needs in the company. The results of the e-learning system research were assessed through employee agent responses from the learning aspect of 84.75% with a good category, seen from the display aspect of 86.05% with the very good category, seen from the aspect of the e-learning system using the Moodle platform of 80, 32% with a good category, and the last one seen from the material aspect in the e-learning system with an interesting concept of 89.82% with the very good category. So the overall assessment of the quality of the e-learning system as a whole is 85.25 with a good category. With this e-learning system, the learning process will be more efficient in displaying learning information needed by company agents in a web-based form and can be accessed by users online as long as they are connected to the internet.